Molecular characterization of antimicrobial susceptibility of Salmonella isolates: First identification of a plasmid carrying qnrD or oqxAB in Taiwan - Cheng-Yen Kao; Chun-An Chen; Yi-Fang Liu; Hsiu-Mei Wu; Chien-Shun Chiou; Jing-Jou Yan; Jiunn-Jong Wu (Journal of Microbiology, Immunology and Infection, 2017)
The aim of this study is to characterize antibiotic-nonsusceptible Salmonella isolates in Taiwan. Methods: A total of 76 Salmonella isolates showing lower susceptibility to cephalosporins or quinolones were identified from 1416 clinical isolates from 1999 to 2008. Minimal inhibitory concentrations for selected antimicrobial agents were tested by the agar dilution method. Antibiotic resistance-related genes were determined by polymerase chain reaction (PCR) combined with sequencing. Southern blotting, conjugation tests, and transformation tests were used to characterize plasmid-mediated quinolone resistance (PMQR) determinants. Results: The observed nonsusceptible phenotypes of 76 isolates were against cefoxitin (57.9%), cefotaxime (43.4%), ceftazidime (40.8%), ceftriaxone (42.1%), cefepime (5.3%), ciprofloxacin (80.3%), and levofloxacin (81.6%). Among 44 cephalosporin-resistant isolates, TEM-1, CMY-2, CMY-14, CTX-M-3-like and CTX-M-15-like determinants were present in 31 (70.5%), 32 (72.7%), 1 (2.3%), 1 (2.3%), and 1 (2.3%) of isolates, respectively. PCR screening for PMQR genes of 62 quinolone-nonsusceptible isolates revealed the presence of qnrS, qnrD, aac(6′)-Ib-cr, and oqxAB in 3 (4.8%), 2 (3.2%), 1 (1.6%), and 10 (16.1%) isolates, respectively. Among 36 isolates showing high resistance to quinolones, S83F/D87N and S83F/D87G amino acid substitutions of GyrA were found in 29 (80.6%) and 6 (16.7%) isolates, respectively. Moreover, among quinolone highly resistant isolates, eight (22.2%) of isolates showed over-expression of the PAβN-sensitive efflux pump. Transformants and transconjugants harboring qnrD- or oqxAB-plasmids showed decreased susceptibility to quinolones. Conclusion: GyrA mutations are the major mechanisms associated with quinolone-resistant Salmonella isolates in Taiwan. Overproduction of efflux pump genes and the presence of qnr and oqxAB play additional roles in reduced susceptibility to quinolones.